2014
DOI: 10.2196/jmir.3578
|View full text |Cite
|
Sign up to set email alerts
|

Tablet, Web-Based, or Paper Questionnaires for Measuring Anxiety in Patients Suspected of Breast Cancer: Patients' Preferences and Quality of Collected Data

Abstract: BackgroundElectronic applications are increasingly being used in hospitals for numerous purposes.ObjectiveOur aim was to assess differences in the characteristics of patients who choose paper versus electronic questionnaires and to evaluate the data quality of both approaches.MethodsBetween October 2012 and June 2013, 136 patients participated in a study on diagnosis-induced stress and anxiety. Patients were asked to fill out questionnaires at six different moments during the diagnostic phase. They were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 19 publications
(14 reference statements)
3
44
1
Order By: Relevance
“…Our participation rate (49%) was similar to rates reported by other tablet-based PROM acquisition studies. [10][11][12][13][14] Tablet-based survey administration permitted both collection of large-scale PROMs data and verification of critical demographic information such as occupational status, education level, and living situation in the population studied. This study highlights the differences between participants and nonparticipants in the routine collection of PROMs.…”
Section: Figurementioning
confidence: 99%
“…Our participation rate (49%) was similar to rates reported by other tablet-based PROM acquisition studies. [10][11][12][13][14] Tablet-based survey administration permitted both collection of large-scale PROMs data and verification of critical demographic information such as occupational status, education level, and living situation in the population studied. This study highlights the differences between participants and nonparticipants in the routine collection of PROMs.…”
Section: Figurementioning
confidence: 99%
“…Touvier et al (2010) showed high preference, equal or better quality of data and considerable cost savings when a web version of a selfadministered anthropometric questionnaire was compared to the paper version. [4] Barentsz et al (2014) showed higher preference web SAQs for younger and more educated patients suspected for breast cancer, [12] and Kongsved et al (2007) showed better completeness of data web SAQs as compared to paper SAQs in evaluation of four clinically validated questionnaires in a hospital setting in Denmark. [13] The success of introducing web SAQs is closely related to how well the population adopt and utilize the technology.…”
Section: Introductionmentioning
confidence: 94%
“…Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,[36][37][38][39][40].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
“…Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,[36][37][38][39][40]. Indeed, ePRO tools of the FACT-B questionnaire with proven reliability are missing so far.…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation